Development of An Environmental Chemistry Module Based on Green Chemistry Principles Through Project Activities - Asyhar, Rayandra; Minarni, Minarni (Pendidikan Kimia FKIP Universitas Jambi, 2024)
This research developed an environmental chemistry module based on green chemistry principles through project activities. The study aimed to describe the development process, validate the product, and assess its effectiveness in teaching. The development followed Lee and Owens' four-step process. Qualitative data from expert feedback informed revisions, while quantitative data from questionnaires were collected. The subjects were 40 chemistry education students. Validation by material experts in two rounds showed scores of 80.76% and 85.38% (valid), improving to 100% and 90.76% (very valid) in the second stage. Design validation by three experts yielded initial scores of 83.4%, 86.7%, and 73.4% (valid), which improved to 100%, 93.3%, and 96.7% (very valid) in the second stage. Student responses rated the module as 84.68% (practical). The Wilcoxon signed ranks test for effectiveness showed a significant p-value of 0.000, indicating improved argumentation abilities and science process skills, which averaged 83.25% (excellent).